Biofilm forming ability of coagulase-positive staphylococci isolated from animals in Ukraine - Shevchenko, M.; Andriichuk, A.; Bilyk, S.; Dovhal, O.; Mazur, T.; Tsarenko, T. (Regulatory Mechanisms in Biosystems, 2023)
Staphylococcal biofilms are an important virulence factor that allows for effective infectious effects and colonization of the animal body. This study was devoted to the evaluation of the biofilm forming ability of different strains of Staphylococcus pseudintermedius and Staphylococcus aureus isolated from animals in Ukraine. In addition, the presence of extracellular adhesin genes icaA and icaD in S. pseudintermedius strains was determined. The density of the biofilms was determined by culturing microorganisms in 96-well plates and staining the resulting structures with crystal violet. The genes responsible for biofilm formation were identified by classical polymerase chain reaction (PCR) using primers selected from the literature. The data obtained from this study showed a direct correlation between the density of the biofilm and the number of viable cells involved in its formation. Thus, 23.1% of S. pseudintermedius strains and 25% of S. aureus strains isolated from dogs demonstrated the ability to form a dense biofilm, while 46.2% of S. pseudintermedius strains and 50% of S. aureus strains formed a weak biofilm. The origin of the isolates had no significant effect on the biofilm characteristics. Coagulase-positive staphylococci obtained from cats did not form dense biofilms. 42.9% of methicillin-resistant Staphylococcus aureus (MRSA) isolates from cows with mastitis had moderate to strong biofilm forming properties. Isolates that showed resistance to three or more antibiotic groups tended to form denser biofilms. In addition, 73.3% of the studied S. pseudintermedius strains were found to contain the icaA gene, and 90% – the icaD gene. A genotypic profile combining both icaA and icaD genes was present in 66.7% of the bacteria, while one strain lacked both genes. Understanding the biofilm forming properties of staphylococcal isolates is important in the context of developing optimal treatment strategies and effective antibiotic use, which will contribute to better control of infections caused by these microorganisms.